Preliminary effectiveness and production time and costs of three-dimensional printed orthoses in chronic hand conditions: an interventional feasibility study - Tanja Oud; Johannes A. Bogaards; Frans Nollet; Merel-Anne Brehm (Medical Journals Sweden, 2024)
Objective: To assess the preliminary effectiveness of three-dimensional printed orthoses compared with conventionally custom-fabricated orthoses in persons with chronic hand conditions on performance of daily activities, hand function, quality of life, satisfaction, and production time and costs. Design: Interventional feasibility study. Subjects: Chronic hand orthotic users (n = 21). Methods: Participants received a new three-dimensional printed orthosis according to the same type as their current orthosis, which served as the control condition. Primary outcome was performance of daily activities (Patient-Reported Outcomes Measurement Information System-Upper Extremity; Michigan Hand Questionnaire). Secondary outcomes were hand function, quality of life, and satisfaction. Furthermore, production time and costs were recorded. Results: At 4 months' follow-up, no significant differences were found between three-dimensional printed orthoses and participants' existing conventional orthoses on activity performance, hand function, and quality of life. Satisfaction with the three-dimensional printed orthosis was significantly higher and the production time and costs for three-dimensional printed orthoses were significantly lower compared with conventional orthoses. The three-dimensional printed orthosis was preferred by 79% of the participants. Conclusions: This feasibility study in chronic hand conditions suggests that three-dimensional printed orthoses are similar to conventional orthoses in terms of activity performance, hand function, and quality of life. Satisfaction, and production time and costs favoured the three-dimensional printed hand orthoses.